Insulin infusion sets associated with adverse events: strategies for improved diabetes education - Neves, Ana Lucia Domingues; Martins, Luiz Eduardo Galvão; Gabbay, Mônica Andrade Lima; Pascali, Paula; de Oliveira, Tiago; Martinazzo, Aldo; Dib, Sérgio Atala; Casarini, Dulce Elena; Aredes, Sebastião Vagner; Tenorio, Fernanda Silva; Cunha, Tatiana Sousa (Frontiers in Medicine, 2023)
Introduction Insulin Infusion Sets (IIS) play a crucial role in ensuring the safe delivery of insulin through a Continuous Subcutaneous Insulin Infusion (CSII) for individuals with Type 1 Diabetes (T1D). Recent advancements in therapy have highlighted the need to address issues such as unexplained hyperglycemia and IIS occlusion. Objective To investigate the adverse events (AEs) associated with IIS that impact the treatment of T1D, with a specific focus on promoting effective educational practices. Methods One hundred and eighteen patients under treatment at the Diabetes Center Insulin Pump Ambulatory, Federal University of São Paulo responded to a semi-structured questionnaire. Over 6 months, a nurse researcher interviewed them via video calls. Results Catheter-related adverse events (AEs) included catheter knots, folding, and accidental traction. AEs associated with cannula use were mainly related to cannula fixation adhesive, insulin leakage, bleeding episodes, and skin problems. The cannula patch tends to detach easily in hot conditions or when used for more than 3 days, leading to local itching. Adhesive glue can cause redness and pain. Insulin leakage typically occurs after the catheter disconnects from the cannula, accidental cannula traction, or beneath the cannula patch. Bleeding has been reported inside the cannula or at the insertion site, resulting in local pain and, in some cases, obstruction of insulin flow. When accidental cannula traction occurs, it is recommended to replace the entire IIS system. In situations involving bleeding, leakage, insulin odor, or unsuccessful attempts to correct hyperglycemic episodes with a “bolus” of insulin, it is advisable to change the IIS system and evaluate appropriate techniques for handling and infusing the device. Moreover, regular inspections of the device and reservoir/cartridge are essential. Conclusion Serious AEs can occur even in cases where the occlusion alarm is not activated, leading to interruptions in insulin flow. Conversely, in less severe situations, alarm activation can occur even in the absence of insulin flow interruption. Accidental catheter traction and catheter bending are commonly encountered in everyday situations, while issues related to the cannula directly affect blood glucose levels. AEs related to the IIS cannula often involve insulin leakage into the skin, bleeding, and skin events attributed to adhesive issues with the cannula.